Sweep Coverage for Boundary of Rectangular Region Using Geometric Approach - Sharma, Ritesh; Kaur, Gurbax (International Journal of Computer Sciences and Engineering, 2025)
There are typical applications where only periodic patrol inspections are sufficient instead of continuous monitoring like in traditional coverage. This periodic monitoring is termed as sweep coverage. In the sweep coverage scenario deployment of static sensor nodes may partially solve the purpose but it suffers from poor efficiency and unnecessary extra overhead. Moreover static sensor network suffers from static sink neighborhood problem as in static sensor network all sensing data from the sensors are relayed to the sink node (base station) through multi hop. As a result, the sensors near to the sink node become the bottleneck since they have to relay the data of other nodes. Once they die, the sink disconnects from the rest of the network while the rest of sensors are still fully operational with sufficient residual energy. To overcome this problem in our work, we proposed Mobile Sink Wireless Sensor Network (MSWSN). We assume that the given region is Rectangular and our aim is to do Sweep Coverage for Boundary of the Region. In Wireless sensor network Sensor node has fixed communication range ( let D be the communication range then Sensor node will cover all the points which lie within D distance from it in all directions ) and therefore to guarantee the coverage of Boundary Mobile sink will not traverse whole of the boundary but visit certain points in the Boundary known as points to Visit ( P1, P2, ----- Pn ). Points to Visit ( P1, P2, ----- Pn ) are to be chosen in such a way that every boundary point lie within the communication range of Mobile sink from at least one points to Visit ( P1, P2, ----- Pn ) and Mobile Sink must visit every edge of the boundary during traversal. Keeping above coverage conditions in mind our main objective is to choose points to Visit ( P1, P2, ----- Pn ) in such a way that the overall length of closed path travelled by the Mobile sink to collect the data is minimum.